Gliosis attenuation in experimental autoimmune encephalomyelitis by a combination of dimethyl fumarate and pregabalin - Hoelz, Amanda Garcia; Bernardes, Danielle; Cartarozzi, Luciana Politti; Oliveira, Alexandre Leite Rodrigues de (Frontiers in Cellular Neuroscience, 2022)
Dysregulated microglia and astrocytes have been associated with progressive neurodegeneration in multiple sclerosis (MS), highlighting the need for strategies that additionally target intrinsic inflammation in the central nervous system. The objective of the present study was to investigate the glial response in experimental autoimmune encephalomyelitis (EAE) induced mice treated with a combination of dimethyl fumarate (DMF) and pregabalin (PGB). For that, 28 C57BL/6J mice were randomly assigned to the five experimental groups: naïve; EAE; EAE-DMF; EAE-PGB; and EAE-DMF+PGB. Pharmacological treatments were initiated with the beginning of clinical signs, and all animals were euthanized at 28 dpi for the lumbar spinal cord evaluation. The results demonstrated a stronger attenuation of the clinical presentation by the combined approach. DMF alone promoted the downregulation of Iba-1 (microglia/macrophages marker) in the ventral horn compared with the nontreated EAE animals (P<0.05). PGB treatment was associated with reduced Iba-1 immunofluorescence in both the dorsal (P<0.05) and ventral horn (P<0.05) compared to EAE vehicle-treated counterparts. However, the combined approach reduced the Iba-1 marker in the dorsal (P<0.05) and ventral (P<0.01) horns compared to nontreated EAE animals and further reduced Iba-1 in the ventral horn compared to each drug-alone approach (P<0.05). In addition, the combination of DMF and PGB reduced activated astrocytes (GFAP) in both the dorsal and ventral horns of the spinal cord to a naïve-like level and upregulated Nrf-2 expression. Taken together, the data herein suggest robust attenuation of the glial response in EAE mice treated with DMF and PGB.